Efficacy of everolimus and letrozole with or without ribociclib in recurrent endometrial cancer: a phase 2 randomized clinical trial - Jeffrey A. How; Shannon N. Westin; Melissa Pham; Barrett Lawson; Minxing Chen; Nidhi Tandon; Ying Yuan; Rugang Zhang; Amir A. Jazaeri; Anil K. Sood; Michaela Onstad Grinsfelder; Kathleen M. Schmeler; et al. (Nature Communications, 2026)
Abstract In this phase II trial, patients with endometrial cancer (EC) were randomized to everolimus/letrozole with (experimental arm) or without ribociclib (control arm) (ClinicalTrials.gov Identifier: NCT03008408). The primary endpoint was progression-free survival (PFS). Secondary endpoints included toxicity, overall survival (OS), objective response rate (ORR), and clinical benefit rate (CBR). For all-comers, there was no difference in PFS (HR 0.78, 95% CI 0.4-1.4, p = 0.38), OS (HR 0.8, 95% CI 0.4-1.5, p = 0.46), ORR (44.1% vs 25.7%, p = 0.11), or toxicity-related treatment discontinuation (4 [8.6%] vs 3 [11.4%], p = 0.22). Among those with prior endocrine therapy, ORR was higher in the experimental arm (61.5% vs 0.0%, p < 0.001). Within the experimental arm, CTNNB1 mut tumors were associated with improved PFS (HR 0.27, 95% CI 0.1-0.7, p = 0.006) and OS (HR 0.24, 95% CI 0.1-0.7, p = 0.004) compared to those with non- CTNNB1 mut tumors. Despite no survival improvement in all-comers, addition of ribociclib to everolimus/letrozole may improve efficacy in patients with prior endocrine therapy and cases with CTNNB1 mut tumors may have prolonged response.